2016
DOI: 10.1021/acs.molpharmaceut.5b00947
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and 111In–Oxine Labeling of Murine NK Cells for Assessment of Cell Trafficking in Orthotopic Lung Tumor Model

Abstract: A non-invasive in vivo imaging method for NK cell trafficking is essential to gain further understanding of the pathogenesis of NK cell mediated immune response to the novel cancer treatment strategies, and to discover the homing sites and physiological distribution of NK cells. Although human NK cells can be labeled for in vivo imaging, a little is known about the murine NK cell labeling and its application in animal models. This study describes the isolation and ex-vivo radiolabeling of murine NK cells for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“… 5 More recently, it has regained attention for its ability to directly label and track a variety of immune cells. 6 11 With the growing availability of PET, focus has shifted towards the development of PET tracers for cell labelling. PET imaging offers higher sensitivity than SPECT imaging as well as improved spatial resolution and quantification in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“… 5 More recently, it has regained attention for its ability to directly label and track a variety of immune cells. 6 11 With the growing availability of PET, focus has shifted towards the development of PET tracers for cell labelling. PET imaging offers higher sensitivity than SPECT imaging as well as improved spatial resolution and quantification in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Cell labeling with [ 111 In]­In-oxine is fast and with rather high loading efficiency. However, toxicity of oxine and leakage of the radionuclide from the cell are major drawbacks, as they can result in a high background signal during imaging. Here we have shown that although the NP labeling efficiency is lower, we could achieve similar specific activity per cell and improved radiolabel retention. Radiolabeling of PLGA NPs and other NP platforms have been previously studied for different applications, from in vivo tracking of the NPs to targeting of immune cells for therapeutic purposes. For example, Sirianni et al used fluorine-18-labeled biotin coupled to avidin-PLGA NPs to measure NP delivery in rat brain with PET .…”
Section: Discussionmentioning
confidence: 85%
“…They showed that labeling with 0.011 MBq of 111 in-oxine per 10 6 murine NK cells provided optimal labeling efficiency without affecting cell viability or functionality. 94 a total of 1 ×10 6 freshly isolated and labeled cells were then re-infused in a human lung cancer mouse model. Mice with lung cancer showed higher tumor uptake of labeled nK cells than control mice.…”
Section: Imaging Tumor-infiltrating Nk Cellsmentioning
confidence: 99%
“…as a control, mice that received no nK cells were irradiated and showed a high tumor burden 72 hours after injection, suggesting that the combination of both radiation and nK cell injection has the best antitumor effect in this mouse model. 94 Passive incorporation in the cell membrane despite the lower translational potential in humans, optical imaging can be performed in pre-clinical models to evaluate NK cell trafficking with no radiation exposure to operator. To this purpose, Tavri et al used near-infrared dye did (1,19-dioctadecyl-3,3,39,39tetramethyl-indodicarbocyanine) to label nK cells targeting epithelial cell adhesion molecule antigen in human prostate cancer xenografts in rats.…”
Section: Imaging Tumor-infiltrating Nk Cellsmentioning
confidence: 99%